ONTOLOGY OF TERRITORIALITY: THE EIGHTEENTH CONTRADICTION OF CAPITALISM? - Angelo Turco (Bollettino della Società Geografica Italiana, 2019)
Globalitarian capitalism develops a network of contradictions of geographical nature. Among these contradictions it may shows the transcalarity heterotopias and competitive homologation, both linked to the dialectic unhomogeneity/homogeneity analyzed by D. Harvey. The capitalism devel-ops a peculiar relation with ontological territoriality through its sacredness. The economic theology (Weber, Benjamin) linked with political theology (Schmitt) and to the state production modes (Lefebvre), lays the foundations for a ontological desaster that meet the ecological desaster, developing the eighteenth contradiction of capitalism.